Korelasi Antara Kadar Hemoglobin Terhadap Pola Hidup Supir Bus Di Terminal Arjosari Malang - Aditia, Fransiska Ayu (; Vol 10 No 1 (2024): JURNAL KESEHATAN BHAKTI HUSADADO - 10.37848/jurnal.v10i1.203, 2024)
Hemoglobin is a protein found in red blood cells. Low hemoglobin levels can cause anemia. The purpose of this study is to find the hemoglobin level and to find whether there is a relationship between age, sleep duration, the number of cigarettes consumed, and the hemoglobin level in the bus driver at the Arjosari terminal in Malang. This research is a quantitative descriptive research. The sampling technique used is purposive sampling. Hemoglobin levels are checked by the POCT (Point Of Care Testing) method using the Easy Touch hemoglobin tool. The normality values of hemoglobin levels in adult men are 13 g/dl to 17 g/dl. The number of respondents obtained was 20 responses to the male. The lowest grade value was 11.2 g/dl, and the highest was 16.8 g/dl. The conclusion of this study is the results of hemoglobin level examination in bus drivers, in which 14 respondents (70%) have normal hemoglobin levels, and in 6 respondents (30%) have low hemoglobin levels. There was a significant relationship between age, sleep duration, and the number of cigarettes consumed with hemoglobin levels in bus drivers at the Arjosari terminal in Malang.